Association of genetic risk and lifestyle with incident adult-onset asthma in the UK Biobank cohort. Issue 2 (11th April 2023) - Liang, Huaying; Jing, Danrong; Zhu, Yiqun; Li, Dianwu; Zhou, Xin; Tu, Wei; Liu, Hong; Pan, Pinhua; Zhang, Yan
Background: Both genetic and lifestyle factors contribute to the development of asthma, but whether unfavourable lifestyle is associated with similar increases in risk of developing asthma among individuals with varying genetic risk levels remains unknown. Methods: A healthy lifestyle score was constructed using body mass index, smoking status, physical activities and dietary pattern to further categorise into ideal, intermediate and poor groups. Genetic risk of asthma was also categorised as three groups based on the tertiles of polygenic risk score established using 212 reported and verified single-nucleotide polymorphisms of European ancestry in the UK Biobank study. We examined the risk of incident asthma related with each lifestyle level in each genetic risk group by Cox regression models. Results: Finally, 327 124 participants without baseline asthma were included, and 157 320 (48.1%) were male. During follow-up, 6238 participants (1.9%) developed asthma. Compared to ideal lifestyle in a low genetic risk group, poor lifestyle was associated with a hazard ratio of up to 3.87 (95% CI, 2.98–5.02) for developing asthma in a high genetic risk group. There was interaction between genetic risk and lifestyle, and the population-attributable fraction of lifestyle and genetic risk were 30.2% and 30.0% respectively. Conclusion: In this large contemporary population, lifestyle and genetic factors jointly play critical roles in the development of asthma, and the effect values of lifestyle on incident adult-onset asthma were greater than that of genetic risk. Our findings highlighted the necessity of a comprehensive intervention for the prevention of asthma despite the genetic risk. In this large contemporary population, lifestyle and genetic factors jointly play critical roles in the development of asthma, and poor lifestyle had a greater effect than genetic risk https://bit.ly/3PD7Qhq